The Comparison of Using Andesite Waste Powder and Fly Ash in Concrete - Hakan Ceylan; Metin Davraz (Doğal Afetler ve Çevre Dergisi, 2019)
Andesite stone is widely used in civil engineering and architectural applications in Turkey. The production, cutting and polishing of the andesite stone by mining methods causes a large amount of waste. Some of them are big particular waste that is taken off pit and factories. And the others are powder waste derived during cutting in factories. These are wasted and not reclaimed. Andesite contains SiO2 as the main component. Therefore, andesite may have pozzolanicity and thus may be used as mineral additive in concrete. In this study the usage of andesite waste powder as mineral additive in concrete is compared with F type fly ashes. In order to estimate the status of mineral additives in various replacement levels; the 28 and 90 days compressive strengths of concrete specimens were tested by preparing concrete specimens in different cement dosages. For C40/50 strength class, the optimum replacement rate of andesite waste powder was determined as 10% at curing ages of 28 and 90 days. The results of this study show that andesite waste powder can be used as mineral additive in concrete such as fly ash. The usage of andesite waste powder as a mineral additive at the optimal replacement ratios can achieve savings of, 20 kg cement for C40/50, 46 kg of cement for C55/67, and 52 kg of cement for C70/85.